Inhibition of eEF2K synergizes with glutaminase inhibitors or 4EBP1 depletion to suppress growth of triple-negative breast cancer cells - YoungJun Ju (Nature Portfolio, 2021)
Abstract The eukaryotic elongation factor-2 kinase, eEF2K, which restricts protein translation elongation, has been identified as a potential therapeutic target for diverse types of malignancies including triple negative breast cancer (TNBC). However, the contexts in which eEF2K inhibition is essential in TNBC and its consequences on the proteome are largely unknown. Here we show that genetic or pharmacological inhibition of eEF2K cooperated with glutamine (Gln) starvation, and synergized with glutaminase (GLS1) inhibitors to suppress growth of diverse TNBC cell lines. eEF2K inhibition also synergized with depletion of eukaryotic translation initiation factor 4E-binding protein 1 (eIF4EBP1; 4EBP1), a suppressor of eukaryotic protein translation initiation factor 4E (eIF4E), to induce c-MYC and Cyclin D1 expression, yet attenuate growth of TNBC cells. Proteomic analysis revealed that whereas eEF2K depletion alone uniquely induced Cyclin Dependent Kinase 1 (CDK1) and 6 (CDK6), combined depletion of eEF2K and 4EBP1 resulted in overlapping effects on the proteome, with the highest impact on the ‘Collagen containing extracellular matrix’ pathway (e.g. COL1A1), as well as the amino-acid transporter, SLC7A5/LAT1, suggesting a regulatory loop via mTORC1. In addition, combined depletion of eEF2K and 4EBP1 indirectly reduced the levels of IFN-dependent innate immune response-related factors. Thus, eEF2K inhibition triggers cell cycle arrest/death under unfavourable metabolic conditions such as Gln-starvation/GLS1 inhibition or 4EBP1 depletion, uncovering new therapeutic avenues for TNBC and underscoring a pressing need for clinically relevant eEF2K inhibitors.